Analysis of lower limb work-energy patterns in world-class race walkers. Issue 10 (19th May 2017) - Hanley, Brian; Bissas, Athanassios
ABSTRACT: The aim of this study was to analyse lower limb work patterns in world-class race walkers. Seventeen male and female athletes race walked at competitive pace. Ground reaction forces (1000 Hz) and high-speed videos (100 Hz) were recorded and normalised joint moments, work and power, stride length, stride frequency and speed estimated. The hip flexors and extensors were the main generators of energy (24.5 J (±6.9) and 40.3 J (±8.3), respectively), with the ankle plantarflexors (16.3 J (±4.3)) contributing to the energy generated during late stance. The knee generated little energy but performed considerable negative work during swing (−49.1 J (±8.7)); the energy absorbed by the knee extensors was associated with smaller changes in velocity during stance ( r = .783, P < .001), as was the energy generated by the hip flexors ( r = −.689, P = .002). The knee flexors did most negative work (−38.6 J (±5.8)) and the frequent injuries to the hamstrings are probably due to this considerable negative work. Coaches should note the important contributions of the hip and ankle muscles to energy generation and the need to develop knee flexor strength in reducing the risk of injury.